READING AND SHARING IN ENGLISH CORNER TO STIMULATE GRADE ELEVEN STUDENTS’ INTEREST IN ENGLISH SPEAKING PRACTICE ON ODD SEMESTER IN ACADEMIC YEAR 2022/2023 - Sakti Hasibuan, Edral (BRIGHT VISION Journal of Language and Education, 2024)
The problem faced in teaching English at SMKN 1 Batangtoru is the students’ low interest to speak English. This is caused by the lack of vocabulary, space for practice and other factors. To solve the problem, the researcher did the research by using English Corner in stimulating students’ interest to speak. This research aimed at: (1) improving students’ speaking interest through English Corner; (2) explaining the factors that caused improvement of students’ speaking skill.This research was a classroom action research, that consisted of two cycles. Every cycle consisted of four phases, namely: plan, action, observation, and reflection. The instrument used to collect data are observation sheet, field note, and task. The research showed that using English Corner could improve students’ speaking interest. It could be seen from the result of the observation as a whole. The improvement of students’ speaking interest is influenced by some factors: material, teachers’ approach, media, strategy, classroom activity and classroom management. Thus, the researcher intends to continue using English Corner in his own classes and would like to suggest other English teachers also to implement it in their classes.